The Effect of Interval Training on the Speed ​​of 50 Meter Freestyle Swimming in Female Athletes - Herlinda Tri Wijayanti; Bhayu Billiandri (Universitas Negeri Semarang, 2026)
The 50-meter freestyle swimming speed is an important indicator of sprint swimming performance, so effective training methods are needed to improve the performance of athletes of training age. This study aims to analyze the effect of interval training on the 50-meter freestyle swimming speed of female athletes from the KU IV Central Swimming Club in Pekalongan. The study used a quantitative, quasi-experimental design with a One-Group Pretest–Posttest Design. The study sample consisted of 30 female athletes selected using a purposive sampling technique based on age group IV criteria and training activity. The study was conducted at the Bening Waterboom Swimming Pool in Pemalang Regency for 16 sessions, with training three times a week. The research instrument used a 50-meter freestyle swimming performance test with time measurements using a stopwatch. Data analysis was performed using normality and homogeneity tests, and paired-samples t-tests at the 0.05 significance level. The results showed that the average pretest score of 57.04 seconds decreased to 55.24 seconds in the posttest. The results of the paired-samples t-test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of interval training on increasing 50-meter freestyle swimming speed. The distribution of performance categories also showed an increase in the number of athletes in the good and adequate categories and a decrease in the poor category after the treatment was administered. This performance improvement was influenced by interval training's ability to enhance speed endurance, technical efficiency, and the anaerobic energy system's performance during sprints. Therefore, interval training can be recommended as an effective training method for improving 50-meter freestyle swimming speed performance in development age athletes.